The New Law: University and Society in Peru - Jaworski, Hélan (1969)
The article criticizes Decree Law No. 17437, enacted on February 18, 1969, which sought to reorganize the Peruvian university system; or rather, the transformation of those essential functions of the university in Peruvian society. The enactment of this law is criticized by the author due to the problems and contradictions it presents, which prevent its effective application in the educational system it intends to affect. Thus, the new law not only reduced the autonomy of the universities, but also minimized student intervention, repressed political activity, limited the academic participation of teachers and, even more seriously, did not take into account the social reality of the country's private and public universities. This is why the author points out that the law under commentary prevents the country's universities from fulfilling their mission of social commitment and criticism with the country's development. In view of this, he proposes that the government reevaluate the law and reformulate it, orienting it towards a dialogue with the university community.